THE IMPORTANCE OF BANK CREDITS FOR AGRICULTURAL FINANCING IN SERBIA - Svetlana Popović; Irena Janković; Stojanović Žaklina (Ekonomika Poljoprivrede (1979), 2018)
Agricultural loans present unutilized bank credit market segment in Serbia. This is not only missed profit opportunity for banks, but also serious deficiency that slows down the development of agriculture and rural areas. Paper uses FADN, NBS and bank balance sheet data in order to analyse supply and demand side of this credit market segment, with the aim to better understand the conditions for its development. Paper recommends better education of producers and lenders. Banks should better understand the requirements of agricultural producers and risks of the production to be able to create tailored credits. Insurance has very important role in specific risk hedging and can facilitate agricultural loans. There is also a need to adjust the conditions for obtaining subsidized loans, while the land size is considered as a key prerequisite for obtaining loans in the situation of large fragmentation of properties.